From the proletariat to the precariat (about the emergence of a new class) - Toshchenko, Zhan T. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted the emergence of a new social class – precariat (from the Latin – precarium) is justified, which still has many features of the protoclass, as it is formed from disparate social groups. It is stated that in Russia, as in many other countries, the social strata have significantly increased, which represent non-standard specific types of employment – temporary, incomplete, partial, seasonal, episodic, fragmented and others. In the same sphere there are also such social communities and groups as migrants, people of free professions (freelancers), part of young people entering into life. An analysis of their social situation allows us to state that all these social communities and social groups, in spite of differences, have common characteristics – instability, and lack of security of their social status. But, as in its time, the proletariat was not a single whole, so the precariat is at the stage of its gradual formation. The reasons for the emergence of the precariat, its structure, its main characteristics are explained. Identify the main features of this protoclass, compared with other social groups, the first sprouts of transformation from the «class in itself» to the «class for oneself» are revealed.
Keywords: society; social and class structure; precariat; class; protoclass; proletariat; labour; labour market; employment; alienation